Maturation of Papillomavirus Capsids - Buck, Christopher B. (American Society for Microbiology, 2005)
The papillomavirus capsid is a nonenveloped icosahedral shell formed by the viral major structural protein, L1. It is known that disulfide bonds between neighboring L1 molecules help to stabilize the capsid. However, the kinetics of inter-L1 disulfide bond formation during particle morphogenesis have not previously been examined. We have recently described a system for producing high-titer papillomavirus-based gene transfer vectors (also known as pseudoviruses) in mammalian cells. Here we show that papillomavirus capsids produced using this system undergo a maturation process in which the formation of inter-L1 disulfide bonds drives condensation and stabilization of the capsid. Fully mature capsids exhibit improved regularity and resistance to proteolytic digestion. Although capsid maturation for other virus types has been reported to occur in seconds or minutes, papillomavirus capsid maturation requires overnight incubation. Maturation of the capsids of human papillomavirus types 16 and 18 proceeds through an ordered accumulation of dimeric and trimeric L1 species, whereas the capsid of bovine papillomavirus type 1 matures into more extensively cross-linked forms. The presence of encapsidated DNA or the minor capsid protein, L2, did not have major effects on the kinetics or extent of capsid maturation. Immature capsids and capsids formed from L1 mutants with impaired disulfide bond formation are infectious but physically fragile. Consequently, capsid maturation is essential for efficient purification of papillomavirus-based gene transfer vectors. Despite their obvious morphological differences, mature and immature capsids are similarly neutralizable by various L1- and L2-specific antibodies.